Jordan Economic Monitor, Fall 2021 : En Route to Recovery - World Bank (World Bank, Washington, DC, 2021)
Jordan’s economy is showing a healthy recovery following a moderate contraction of 1.6 percent in 2020. Notwithstanding the restrictive pandemic measures, the economy managed to grow by 1.8 percent in the first half of 2021. Meanwhile, accommodative monetary policy by the Central Bank of Jordan (CBJ) as well as fiscal policy, continued to play an active role in supporting the economy during the pandemic, while inflation has remained low. Yet, the pandemic has left deep scars on Jordan’s labor market, exacerbating unemployment challenges, particularly for females, and the youth, which remained at an elevated level. Moreover, Jordan’s external accounts has been under pressure, reflecting the combined impact of unfavorable terms of trade, improved domestic demand and continued slack in travel receipts. Despite these pressures, the Central Bank of Jordan has been able to build up its gross foreign reserves during the first nine months of 2021, on the back of timely donor support. Accelerating global recovery, improved vaccine rollouts and near full reopening of the domestic economy are considered major drivers for this year’s growth. The World Bank projects Jordan to grow by 2.2 percent in 2021. Nevertheless, downside risks remain significant, including uneven global recovery, another potential COVID-19 wave, as well as slow recovery of international tourism. Going forward, it is critical for Jordan to enhance domestic vaccination level, balance high quality fiscal adjustment with reforms to attract private investment and improve productivity to enable a resilient recovery that can help boost inclusive and sustained growth and job creation.